Glucose starvation boosts Entamoeba histolytica virulence. - Ayala Tovy; Rivka Hertz; Rama Siman-Tov; Sylvie Syan; Daniela Faust; Nancy Guillen; Serge Ankri (Public Library of Science (PLoS), 2011)
The unicellular parasite, Entamoeba histolytica, is exposed to numerous adverse conditions, such as nutrient deprivation, during its life cycle stages in the human host. In the present study, we examined whether the parasite virulence could be influenced by glucose starvation (GS). The migratory behaviour of the parasite and its capability to kill mammalian cells and to lyse erythrocytes is strongly enhanced following GS. In order to gain insights into the mechanism underlying the GS boosting effects on virulence, we analyzed differences in protein expression levels in control and glucose-starved trophozoites, by quantitative proteomic analysis. We observed that upstream regulatory element 3-binding protein (URE3-BP), a transcription factor that modulates E.histolytica virulence, and the lysine-rich protein 1 (KRiP1) which is induced during liver abscess development, are upregulated by GS. We also analyzed E. histolytica membrane fractions and noticed that the Gal/GalNAc lectin light subunit LgL1 is up-regulated by GS. Surprisingly, amoebapore A (Ap-A) and cysteine proteinase A5 (CP-A5), two important E. histolytica virulence factors, were strongly down-regulated by GS. While the boosting effect of GS on E. histolytica virulence was conserved in strains silenced for Ap-A and CP-A5, it was lost in LgL1 and in KRiP1 down-regulated strains. These data emphasize the unexpected role of GS in the modulation of E.histolytica virulence and the involvement of KRiP1 and Lgl1 in this phenomenon.